PEDAGOGICAL FOUNDATIONS AND EFFECTIVENESS FACTORS OF IMPLEMENTING DIGITAL TECHNOLOGIES IN DRAFTING LESSONS - Raximova Gulsanam Hazrat qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the pedagogical foundations and effectiveness factors of implementing digital technologies in drafting lessons at general secondary schools. The study highlights how modern digital tools—such as computer-aided design (CAD) software, interactive whiteboards, and virtual drawing platforms—enhance students’ spatial thinking, creative abilities, and professional competencies. The integration of digital technologies not only increases learning motivation and efficiency but also aligns the teaching process with the requirements of the digital age. The paper also discusses the methodological principles for organizing digital drafting lessons and the role of teachers in developing digital literacy among students.